Effect of neostigmine on gastroduodenal motility in patients with suspected gastrointestinal motility disorders. Issue 12 (20th September 2015) - Parthasarathy, G.; Ravi, K.; Camilleri, M.; Andrews, C.; Szarka, L. A.; Low, P. A.; Zinsmeister, A. R.; Bharucha, A. E.
Abstract: Background: Acetylcholinesterase inhibitors (ACIs), e.g., neostigmine, are known to increase upper and lower gastrointestinal (GI) motility and are used to treat acute colonic pseudoobstruction. However, their effects on gastroduodenal motility in humans are poorly understood. Our hypotheses were that, in patients with suspected GI motility disorders, neostigmine increases gastric and small intestinal motor activity, and these effects are greater in patients with cardiovagal neuropathy, reflecting denervation sensitivity. Methods: In this open label study, the effects of neostigmine (1 mg intravenously) on gastroduodenal motor activity recorded with manometry were assessed in 28 patients with a suspected GI motility disorder. Cardiovagal function was assessed with the heart rate response to deep breathing and GI transit by scintigraphy. Key Results: The final diagnoses were gastroparesis (6 patients), gastroparesis with intestinal neuropathy (3 patients), intestinal neuropathy or pseudoobstruction (5 patients), functional dyspepsia (6 patients), chronic abdominal pain (3 patients), mechanical small intestinal obstruction (3 patients), and pelvic floor dysfunction (2 patients). Neostigmine increased both antral and intestinal phasic pressure activity ( p < 0.001). Neostigmine increased antral and intestinal pressure activity in 81% and 50% of patients with reduced postprandial antral and intestinal contractile responses to meal, respectively. The antroduodenal pressure response to neostigmine was not higher in patients with cardiovagal dysfunction. Conclusions & Inferences: Neostigmine increased antral and intestinal motor activity in patients with hypomotility, including intestinal dysmotility. These responses to neostigmine were not greater in patients with cardiovagal dysfunction. The use of longer‐acting ACIs for treating antroduodenal dysmotility warrant further study. Abstract : Intravenous neostigmine increased antral and intestinal motor activity in patients with hypomotility, including intestinal dysmotility. These responses to neostigmine were not greater in patients with cardiovagal dysfunction.